Analysis of Forecasting Methods and Models - Pulotova Mokhira Rakhmatiloevna; Muzaffarova Gulsara Otabekovna (Genius Journals, 2022)
Technological processes (TP) of formalin production are characterized by continuity, toxicity of raw materials, product and exhaust gases, fire and explosion hazard, a large number of interrelated input and output parameters, drift of parameters of the formaldehyde synthesis stage, and a long residence time of absorbed components in absorption apparatuses. The main mode of operation of formalin production units is static.
Keywords: regressiya modeli; matematik model